2012
DOI: 10.3109/0886022x.2012.741647
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Recurrent Urinary Tract Infection in Southern Thailand

Abstract: Introduction: Recurrent urinary tract infection (UTI) is one of the major health problems in children because of its high rate of occurrence. Objective: Our aim of the study was to evaluate the prevalence and determine risk factors of recurrent UTI in Thai children. Patients and Methods: The medical records of children aged less than 15 years diagnosed with UTI at the Department of Pediatrics, Songklanagarind Hospital were reviewed. Results: A total of 307 children (144 boys, 163 girls) were followed up for at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(29 reference statements)
1
2
2
1
Order By: Relevance
“…Any detected CAKUT had similar proportions for the ESBL and non-ESBL groups. Although our previous study found CAKUT to be a risk factor for recurrent UTI [21], in this current study recurrent UTI was a risk factor for ESBL UTI, but CAKUT was not an independent risk factor for ESBL UTI. Almost half of our UTI patients were aged more than 2 years, which, in our setting, may be due to the fact that parents of children with symptoms of UTI tend to delay seeking medical care for their children.…”
Section: Discussioncontrasting
confidence: 96%
“…Any detected CAKUT had similar proportions for the ESBL and non-ESBL groups. Although our previous study found CAKUT to be a risk factor for recurrent UTI [21], in this current study recurrent UTI was a risk factor for ESBL UTI, but CAKUT was not an independent risk factor for ESBL UTI. Almost half of our UTI patients were aged more than 2 years, which, in our setting, may be due to the fact that parents of children with symptoms of UTI tend to delay seeking medical care for their children.…”
Section: Discussioncontrasting
confidence: 96%
“…With regard to the recurrence of febrile UTI, a significant association was observed between the presence of VUR and UTI recurrence in this study. In line with our findings, a study involving 307 UTI patients showed that the recurrence was related to reflux 25) . Another study involving children aged <6 years showed a correlation between UTI recurrence and VUR grades 4 and 5 26) .…”
Section: Discussionsupporting
confidence: 92%
“…Vachvanichsanong et al (15) conducted a follow up study for one year to evaluate the prevalence and to determine the risk factors of recurrent UTI in children. In their study, which included all UTI children aged less than 15 years old, over a ten-year period at hospitals, they found that recurrent UTI in normal children was low; while in children with a genitourinary (GU) anomaly or other underlying disease indicating an immune compromised host, the recurrence rates were significantly higher.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary Tract Infection accrues in males more than females in the first month of life (13)(14)(15) and is more common in females from the second month to adulthood. Furthermore, UTI relapse is two or more episodes of infection in a six-month period (16).…”
Section: Introductionmentioning
confidence: 99%